Method of producing amorphous body for use in synthesizing hexagonal ferrite and magnetic powder of hexagonal ferrite
The manufacturing process for hexagonal ferrite magnetic powders, which involves a kneading step followed by granulation and calcination, effectively addresses the issue of composition variation across batches, enhancing the uniformity of magnetic properties.
Patent Information
- Application Number
- JP2023159110
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
AI Technical Summary
Existing methods for producing hexagonal ferrite magnetic powders using the glass crystallization method struggle to achieve uniform composition across production batches, particularly when incorporating strontium as a substituting element, leading to variations in magnetic properties.
A manufacturing process that includes a kneading step to mix raw powder with water, followed by granulation, drying, heating, quenching, and calcination, which helps in reducing composition variations by ensuring high homogeneity of the amorphous body formed.
The proposed method significantly reduces composition variations between production batches, leading to improved uniformity of magnetic properties in the hexagonal ferrite magnetic powders, especially when strontium is used as a substituting element.
Smart Images

Figure 2025050360000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an amorphous body used to synthesize magnetoplumbite-type (M-type) hexagonal ferrite magnetic powder suitable for high-density recording on magnetic recording media, and a method for producing said hexagonal ferrite magnetic powder. [Background technology]
[0002] Hexagonal ferrite magnetic powder is used as a magnetic material that can achieve excellent recording density in coated magnetic recording media for data archives, etc. A typical method for producing this hexagonal ferrite magnetic powder is the so-called glass crystallization method, in which an amorphous body containing the constituent elements of hexagonal ferrite is heated to synthesize hexagonal ferrite crystals.
[0003] Patent Document 1 describes the application of a process of forming raw materials into an aggregated state when an amorphous body for synthesizing hexagonal ferrite is manufactured by a glass crystallization method. Here, the "aggregated state" is a state in which the surfaces of particles are bonded to each other to form an aggregate of two or more particles, or a state in which the surfaces of particles are not in contact with each other but are simply close to each other to form an aggregate of two or more particles (paragraph 0031). As a specific example of forming into an "aggregated state", a method is disclosed in which the raw material mixed powder is put into a pan pelletizer and rolled while spraying water. The pan pelletizer repeats agglomeration so that the raw material powder is bonded to each other while rolling, and gradually becomes a molded body with a spherical shape (paragraph 0072). By synthesizing hexagonal ferrite using the amorphous body obtained by this method, a hexagonal barium ferrite magnetic powder with small compositional variation can be obtained.
[0004] Patent Document 2 describes a method of using a material obtained by mixing raw material powders having a D90 particle size of 1 to 200 μm when manufacturing an amorphous body for synthesizing hexagonal ferrite by a glass crystallization method. This method is also effective in obtaining hexagonal barium ferrite magnetic powder with small composition variation. As for molding the raw material mixed powder, it is taught that a method of adding water and agglomerating it using a pan pelletizer or the like is preferable, as in Patent Document 1 (paragraphs 0054 and 0083). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2014-199870 A [Patent Document 2] JP 2015-26790 A Summary of the Invention [Problem to be solved by the invention]
[0006] As disclosed in Patent Documents 1 and 2, the method of forming raw materials into an aggregated state and the method of using raw powders with adjusted particle size distribution are effective in obtaining hexagonal barium ferrite magnetic powders with small compositional variation using a glass crystallization method. However, in order to control the magnetic properties more precisely, further reduction in compositional variation is required. In particular, in recent years, development of hexagonal barium ferrites with a small amount of strontium added as an element to replace part of barium has been progressing, and the magnetic properties can vary greatly depending on the compounding composition of the replacement element. Therefore, uniformity of the composition between manufacturing batches has become more important than ever, and it has been found that there is still room for improvement in the method of reducing compositional variation.
[0007] An object of the present invention is to provide a manufacturing technique for hexagonal ferrite magnetic powder that is more effective in reducing compositional variation between manufacturing batches than in the past. [Means for solving the problem]
[0008] The above object can be achieved by the following invention. [1] A kneading step of kneading a raw material powder containing a component for forming an amorphous body for synthesizing hexagonal ferrite with water to obtain a kneaded mixture; A granulation step of granulating the kneaded mixture to obtain a granular compact; a heat-melting step of heating the granular compact to obtain a molten compact; a quenching step of quenching the molten body to obtain an amorphous body; A method for producing an amorphous body for synthesizing hexagonal ferrite comprising the steps of: [2] The method for producing an amorphous material for synthesizing hexagonal ferrite according to the above [1], further comprising a drying step of drying the granular compact obtained in the granulation step prior to the heat-melting step. [3] The method for producing an amorphous material for synthesizing hexagonal ferrite according to [1] or [2] above, wherein in the kneading step, water is kneaded in a mixing ratio of 20 parts by mass or more and 35 parts by mass or less per 100 parts by mass of the raw material powder. [4] The method for producing an amorphous material for synthesizing hexagonal ferrite according to any one of [1] to [3] above, wherein the raw material powder contains Ba and Sr for forming an amorphous material for synthesizing strontium-containing hexagonal barium ferrite. [5] A firing step of synthesizing hexagonal ferrite crystals by heating the amorphous material obtained by the method for producing an amorphous material for synthesizing hexagonal ferrite according to any one of [1] to [4] above to obtain a hexagonal ferrite-containing powder; a residual component removing step of removing residual components other than hexagonal ferrite from the hexagonal ferrite-containing powder; A method for producing a hexagonal ferrite magnetic powder having the above structure. [6] A preliminary heat treatment step of heating the amorphous material containing Ba and Sr obtained by the method for producing an amorphous material for synthesizing hexagonal ferrite described in [4] above to a temperature range of 500 ° C. to 570 ° C. to obtain an intermediate material; a firing step of synthesizing hexagonal ferrite crystals by heating the intermediate to a temperature range of 600° C. to 670° C. to obtain a hexagonal ferrite-containing powder; a residual component removing step of removing residual components other than hexagonal ferrite from the hexagonal ferrite-containing powder; The method for producing a hexagonal ferrite magnetic powder having the above structure. [7] A method for producing a hexagonal ferrite magnetic powder according to the above [6], which obtains a strontium-containing hexagonal barium ferrite magnetic powder having a Sr / (Ba+Sr) molar ratio of 0.01 to 0.30. Effect of the Invention
[0009] According to the manufacturing technique of the ferrite magnetic powder of the present invention, it is possible to obtain a more excellent effect than the conventional technique in terms of reducing the compositional variation between manufacturing batches. The present invention is particularly useful in controlling the composition with high precision in the manufacturing of hexagonal ferrite magnetic powder having a structure in which a part of barium is replaced with another element (e.g., strontium), and can contribute to improving the uniformity of the magnetic properties improved by the replacement element. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a process diagram illustrating a typical conventional manufacturing process for producing hexagonal ferrite magnetic powder by a glass crystallization method. [Diagram 2] FIG. 2 is a process diagram illustrating a typical manufacturing process according to the present invention when producing hexagonal ferrite magnetic powder by a glass crystallization method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The hexagonal ferrite, which is the object of the manufacturing method of the present invention, has a basic structure of the chemical formula AO·6Fe2O3. The A element in the above chemical formula is Ba, Sr, Pb, Ca, etc. For hexagonal ferrite for magnetic recording media, barium ferrite in which the majority of the A element is Ba, or strontium ferrite in which the majority of the A element is Sr is generally used. Depending on the required characteristics, some of the Fe sites may be replaced with metal elements such as Co, Zn, Ti, Sn, Nb, and V. In addition, the hexagonal ferrite magnetic powder may contain Bi, Al, rare earth elements, etc. as necessary as elements other than the constituent elements of the crystal lattice.
[0012] FIG. 1 illustrates a typical manufacturing process in the conventional method for manufacturing hexagonal ferrite magnetic powder by glass crystallization. The raw powder is granulated by a pan pelletizer or the like to obtain a granulated compact. In this granulation process, the raw powder particles are usually aggregated by "aggregation" as disclosed in Patent Documents 1 and 2 to obtain a granular compact. After drying this granular compact as necessary, the temperature is raised to about 1000 to 1600 ° C to heat and melt it, and a molten body is obtained. This molten body contains components that become hexagonal ferrite powder and components necessary to generate an amorphous body. Next, the molten body is quenched by, for example, a gas atomization method to obtain an amorphous body. This amorphous body is fired at, for example, about 450 to 900 ° C to synthesize hexagonal ferrite, and a hexagonal ferrite-containing powder is obtained. This hexagonal ferrite-containing powder contains residual components other than hexagonal ferrite, so the target hexagonal ferrite magnetic powder can be obtained by undergoing a process of removing the residual components, for example by washing with an aqueous acetic acid solution.
[0013] FIG. 2 illustrates a typical manufacturing process according to the present invention when manufacturing hexagonal ferrite magnetic powder by a glass crystallization method. A major difference from the conventional method shown in FIG. 1 is that a "kneading step" is applied in which water is added to the raw material powder and kneaded to form a kneaded product. The kneaded product is granulated to obtain a granular compact. The subsequent steps can be performed using a conventionally known method such as that shown in FIG. 1. It has been found that by using the granular compact derived from the kneaded product as a material for forming a molten product, the effect of reducing the composition variation between manufacturing batches of the hexagonal ferrite magnetic powder finally obtained when the subsequent steps are performed in the same manner as the conventional method is superior to that of the conventional method.
[0014] The granular compact derived from the kneaded product is different from the granular compact obtained in the granulation process by agglomeration described above in that the particles of the raw material powder are mixed with water in the kneading process, and therefore the constituent particles are denser and the distribution of the contained components is very homogeneous. This is presumably what contributes greatly to the improvement of the effect of reducing the compositional variation.
[0015] The matters that define the present invention will be described below. [Raw material powder] A raw powder containing components for forming an amorphous body for synthesizing hexagonal ferrite is prepared. The "components for forming an amorphous body for synthesizing hexagonal ferrite" include the constituent elements of the desired hexagonal ferrite magnetic powder (hereinafter sometimes referred to as "magnetic powder constituent elements") and elements that exhibit the function of generating an amorphous body by quenching (hereinafter sometimes referred to as "amorphous body generating elements"). As described above, the A element of hexagonal ferrite with the basic structure of the chemical formula AO·6Fe2O3 includes Ba, Sr, Pb, Ca, etc., and the Fe site replacement elements include Co, Zn, Ti, Sn, Nb, V, etc. If necessary, Bi, Al, rare earth elements, etc. are added as magnetic powder constituent elements. On the other hand, the amorphous body generating elements include Ba, Sr, Ca, B, etc. The above Ba, Sr, and Ca are magnetic powder constituent elements and amorphous body generating elements at the same time. Carbonates, oxides, hydroxides, etc. can be used as supply materials for these necessary elements, and it is preferable to construct the raw powder by thoroughly mixing each substance. The mixing operation can be performed, for example, by using a mixer with stirring blades such as a Henschel mixer, or a container-rotating mixer such as a V-type mixer. In determining the blending amounts of each substance that constitutes the raw material powder, the blending is designed taking into consideration the loss of magnetic powder constituent elements such as Ba, Sr, and Ca in the residual component removal process after sintering.
[0016] [Mixing process] The raw powder and water are kneaded to obtain a kneaded product. This process is important in the present invention. Here, "kneading" refers to the operation of mixing the powder and liquid medium and at the same time applying an external force to the mixed object to perform a "kneading" action, thereby mixing the powder particles and the liquid medium in a highly uniform state and forming a clay-like substance (kneaded product). Here, water can be used as the liquid medium.
[0017] As the kneading machine, a known one can be used. For example, a kneader with a rotating fixed stirring blade, a planetary mixer with a stirring blade rotating and revolving around its axis, an extruder with a stirring operation while heating and pressurizing in addition to kneading, and other general kneading machines can be used. From the viewpoint of ensuring the uniformity of the mixture of the kneaded material obtained, it is preferable to use a batch type kneader, and from the viewpoint of ensuring the uniformity of the mixture within the same batch, it is more preferable to use a batch type kneader having multiple blades. The operating conditions and operating time of the kneader can be set to conditions and times that allow visual confirmation that the raw material powder and water are mixed uniformly and that the kneaded material has viscosity. It is preferable to use pure water for the water used in kneading in order to reduce the impurity concentration in the magnetic powder obtained as much as possible. In kneading, it is effective to adjust the clearance between the stirring blade and the wall surface to an appropriate size in order to improve the yield. In addition, a water-cooled jacket may be provided on the kneader body in order to adjust the temperature of the kneaded material.
[0018] The amount of water added during kneading is set so as to give the kneaded product an appropriate viscosity and flexibility. Specifically, for example, the blending ratio of the raw powder and water can be set within a range of 20 parts by mass to 35 parts by mass of water to be mixed, more preferably within a range of 25 parts by mass to 33 parts by mass of water, per 100 parts by mass of raw powder. If the proportion of water is too small, the water does not sufficiently spread between the powder particles, and it is difficult to achieve a highly uniform state between the powder particles and the water. In this case, composition deviation occurs between the granular compacts in the next granulation process, which causes unevenness in the composition distribution in the subsequent melt. If the proportion of water is too high, the kneaded product obtained becomes too soft, making it difficult to form a granular compact in the next granulation process, or causing a decrease in yield due to a part of the kneaded product or granular compact adhering to the wall surface of the conveying path.
[0019] The substances that make up the raw powder may contain water of crystallization. In that case, the water as crystallization water is considered to be part of the mass of the raw powder and is excluded from the mass of the water to be mixed.
[0020] [Granulation process] The kneaded material obtained in the kneading step is granulated to obtain a granular compact. Granulating the kneaded material makes it easier to transport, and prevents problems such as the material adhering to the feed tube when the material is fed into the melting furnace in the next step. The shape of the granular compact is preferably a smooth shape with no vertices or ridges of a polyhedron on its surface, and is most preferably a spherical shape close to a perfect sphere, in order to minimize adhesion to the transport path and the feed tube of the melting furnace. As a granulator for granulation, a granulator having an extrusion mechanism using a screw and a molding mechanism for forming spherical particles using rollers (hereinafter sometimes referred to as a "rounding machine") or an extrusion type granulator can be used. In order to obtain a spherical granular compact as close to a perfect sphere as possible, it is preferable to use a rounding machine.
[0021] The granular compact obtained according to the present invention has been subjected to a kneading process, and therefore has higher mechanical strength and improved transportability between devices compared to compacts obtained in the granulation process by aggregation as described in Patent Documents 1 and 2. Therefore, there is an advantage in that a decrease in yield caused by the granular compact crumbling and part of it falling off during transport can be suppressed.
[0022] [Drying process] The granular compact contains moisture. Although the granular compact according to the present invention has improved mechanical strength as described above, if the granular compact with a high moisture content is advanced to the next step, depending on the specifications of the conveying device, the granular compact may adhere to the conveying path or the charging tube of the melting furnace, which may cause trouble. Therefore, before advancing to the next step of the heating and melting step, a drying step for drying the granular compact can be inserted as necessary. In the drying step, a method of heating and holding the granular compact in air at, for example, 100°C to 500°C, more preferably 200°C to 400°C, can be applied. It is preferable to dry the granular compact so that the moisture concentration in the granular compact obtained after drying is 2.0 mass% or less as measured by an infrared moisture meter.
[0023] [Heat melting and rapid cooling process] The granular compact obtained in the granulation step is heated and melted by a known method to form a melt. The temperature during melting is preferably 1000°C or higher and 1600°C or lower. The resulting melt is quenched to obtain an amorphous body. The quenching step is preferably performed by a gas atomizing method or a twin-roll method. In this manner, an amorphous body that is advantageous for synthesizing hexagonal ferrite with less compositional variation than conventional methods can be obtained.
[0024] [Preliminary heat treatment process] The above amorphous body is usually directly subjected to a sintering process and used to synthesize hexagonal ferrite. According to the knowledge of the present applicant, it has been found that a preliminary heat treatment prior to the sintering process can be advantageous in improving magnetic properties such as the magnetocrystalline anisotropy constant Ku. In particular, in the manufacture of strontium-containing hexagonal barium ferrite magnetic powder having a Sr / (Ba+Sr) molar ratio of 0.01 to 0.30, the effect of including a preliminary heat treatment process is large. Therefore, it is preferable to perform a preliminary heat treatment process as necessary to form an intermediate. This preliminary heat treatment can be performed under conditions in which the amorphous body is heated to a temperature range of, for example, 500°C to 570°C. The holding time in that temperature range may be, for example, 10 hours or more. In this preliminary heat treatment, it is considered that most of the divalent Fe contained in the amorphous body obtained by quenching is oxidized to trivalent Fe. It is believed that by using an intermediate in which trivalent Fe has already been formed, the reaction that promotes the oxidation of divalent Fe to trivalent Fe during sintering is significantly reduced, which is advantageous for the synthesis of strontium-containing hexagonal barium ferrite magnetic powder with improved magnetic properties such as the magnetocrystalline anisotropy constant Ku.
[0025] [Firing process] The amorphous body or the intermediate body that has been subjected to the preliminary heat treatment is sintered to synthesize hexagonal ferrite crystals. A known method can be applied to this sintering process. For example, it is preferable to adopt a condition in which the material is heated in an air atmosphere at a temperature range of 580°C to 750°C. It is more preferable to heat the material in an air atmosphere at a temperature range of 600°C to 670°C.
[0026] [Residual component removal process] In the hexagonal ferrite-containing powder obtained in the sintering process, many unnecessary components including amorphous generating elements remain as residual components other than hexagonal ferrite, so it is necessary to remove the residual components. The removal of the residual components can be performed by stirring the hexagonal ferrite-containing powder obtained by sintering, for example, in an aqueous acetic acid solution. It is more preferable that the liquid temperature of the aqueous acetic acid solution is, for example, 50°C or higher. In this way, it is possible to obtain a hexagonal ferrite magnetic powder with less compositional variation between production batches than in the past. This hexagonal ferrite magnetic powder also has improved homogeneity in the distribution of powder composition within the same production batch.
[0027] After the residual component removing step, the ferrite particles may be subjected to, for example, wet crushing as required, after which an aluminum hydroxide layer may be formed on the surface of the ferrite particles. Alternatively, dry crushing may be performed as a finishing treatment. EXAMPLES
[0028] [Example 1] (Manufacturing of hexagonal ferrite magnetic powder) 28.0 kg of boric acid H3BO3 powder (for industrial use), 51.7 kg of barium carbonate BaCO3 powder (for industrial use), 4.30 kg of strontium carbonate SrCO3 powder (for industrial use), and 33.7 kg of iron oxide Fe2O3 powder (for industrial use) were weighed out and mixed using a Henschel mixer (FM mixer manufactured by Mitsui Miike Machinery Co., Ltd.) to obtain 117.7 kg of raw material powder.
[0029] 117.7 kg of the obtained raw powder was placed in a kneader (Pam Apex Mixer, WB type, manufactured by Pacific Machinery Co., Ltd.), and while adding pure water with a spray device attached to the device, the large blade rotation speed was set to 80 rpm and the small blade rotation speed was set to 120 rpm, and kneaded for 30 minutes to obtain a kneaded product (kneading process). The total amount of pure water added was 34.1 kg. The total amount of water added to 100 parts by mass of raw powder is (34.1 / 117.7) x 100 = 29.0 parts by mass.
[0030] The kneaded material was granulated into spheres with a diameter of 11 mm using a rounding machine (PT-6015A, manufactured by Freund Turbo) to obtain a granular compact (granulation process). The granular compact was dried in air at 270°C for 14 hours (drying process). The moisture concentration of the granular compact after the drying process was measured with an infrared moisture meter (MX-50, manufactured by AND Co., Ltd.) and was found to be 0.6% by mass.
[0031] The granular compact after the drying process was melted in a melting furnace using a platinum crucible. The temperature was raised to 1400°C and held for 60 minutes while stirring to obtain a melt in which the raw material was in a completely molten state (heating and melting process). Next, the melt (molten metal) was discharged from a nozzle into a gas phase space in an atmospheric air by a gas atomizing method and quenched to obtain an amorphous body (quenching process). The composition of this amorphous body was analyzed. The composition analysis will be described later.
[0032] The obtained amorphous body was heated and held in air at 530°C for 72 hours to obtain an intermediate (preliminary heat treatment step).The intermediate was then heated and held in air at 630°C for 60 minutes to crystallize the intermediate, thereby obtaining a hexagonal ferrite-containing powder (sintering step).
[0033] The obtained hexagonal ferrite-containing powder contains residual substances mainly composed of barium borate in addition to hexagonal ferrite. In order to remove the residual substances, the hexagonal ferrite-containing powder obtained in the firing process was immersed in a 10% by mass aqueous solution of acetic acid heated to 60°C and held for 1 hour while stirring, and subjected to acid washing to dissolve the residual substances in the liquid. Thereafter, solid-liquid separation was performed by filtration, and the powder was washed by adding pure water (residual component removal process).
[0034] Pure water was added to the solids (hexagonal ferrite magnetic powder) obtained in the residual component removal step, and the mixture was stirred and wet-disintegrated with a star mill. An aluminum chloride aqueous solution was added to the slurry containing the solids after wet disintegration. The amount of Al added by aluminum chloride was 3.3 parts by mass in terms of Al(OH)3 per 100 parts by mass of the solids. The slurry after the addition of the aluminum chloride aqueous solution was stirred at 40°C for 10 minutes. The pH of this slurry was in the range of 3.0 to 4.0. Thereafter, sodium hydroxide was added to adjust the pH to 8.0 to 9.0, and the mixture was further stirred at 40°C for 10 minutes to form a layer of aluminum hydroxide, which is a reaction product, on the surface of the solid particles (hexagonal ferrite magnetic particles). Thereafter, solid-liquid separation was performed by filtration, pure water was added, and the mixture was washed with water until the conductivity of the washed liquid (filtrate) was 10 μS / cm or less. After washing with water, the mixture was dried in air at 110°C for 12 hours. In this way, a dry powder was obtained in which the surfaces of the hexagonal ferrite particles were coated with aluminum hydroxide.
[0035] As a finishing treatment, the obtained dry powder was fed into an impact mill (Fine Impact Mill AVIS-150 manufactured by Mill Systems Co., Ltd.) at a feed rate of 150 g / min, and dry-disintegrated at a rotation speed of 9750 rpm with a gap of 1 mm between the tip of the rotor pin and the stator base of the impact mill. The disintegration conditions were set within the range of appropriate conditions obtained by preliminary experiments. In this way, the hexagonal ferrite magnetic powder in Example 1 was obtained. The composition of this hexagonal ferrite magnetic powder was analyzed.
[0036] (composition analysis) The composition of the amorphous body and the hexagonal ferrite magnetic powder after the finishing treatment was analyzed using an Agilent Technologies Inc. high-frequency induction plasma emission spectrometer ICP (720-ES). The measurement wavelength for each metal element was selected according to the composition of the magnetic powder to be analyzed, so that there was no interference from the spectrum of other elements and the linearity of the calibration curve could be obtained. The Sr / (Ba+Sr) molar ratio was calculated from the quantitative values obtained. It is known that the Sr / (Ba+Sr) molar ratio affects the magnetic properties of magnetic recording media. In this specification, the compositional variation between manufacturing batches is evaluated based on the measured Sr / (Ba+Sr) molar ratio for each example. In Example 1, the Sr / (Ba+Sr) molar ratio of the amorphous body was 0.203, and the Sr / (Ba+Sr) molar ratio of the finally obtained hexagonal ferrite magnetic powder was 0.0913. The results are shown in Table 1.
[0037] [Examples 2 to 6] In Examples 2 to 6, hexagonal ferrite magnetic powder was manufactured by carrying out processes from the preparation of raw material powder to the finishing process under the same conditions as in Example 1. That is, Examples 1 to 6 correspond to each manufacturing batch carried out under the same manufacturing conditions. The Sr / (Ba+Sr) molar ratio was determined for each of the amorphous bodies and hexagonal ferrite magnetic powders obtained in Examples 2 to 6 by the same analytical method as in Example 1. The results are shown in Table 1. Table 1 also shows the difference MAX-MIN between the maximum and minimum values and the standard deviation σ determined from the Sr / (Ba+Sr) molar ratio values for the amorphous bodies and hexagonal ferrite magnetic powders of Examples 1 to 6.
[0038] [Comparative Example 1] In Example 1, except that the kneading step was not performed and the granulation step was performed in the following manner to produce a granular compact, an amorphous body was produced, a hexagonal ferrite magnetic powder was produced using the amorphous body, and a composition analysis was performed in the same manner as in Example 1. That is, the production process of Comparative Example 1 was carried out from the production of the raw material powder to the finishing process by adopting the granulation step described below instead of the kneading step and granulation step of Example 1.
[0039] (granulation process) The raw material powder prepared in the same manner as in Example 1 was charged into a pan pelletizer and rolled while spraying pure water to obtain granular compacts with an average particle size of about 20 mm and a diameter of 1 mm to 40 mm.
[0040] In Comparative Example 1, the Sr / (Ba+Sr) molar ratio of the amorphous body was 0.197, and the Sr / (Ba+Sr) molar ratio of the finally obtained hexagonal ferrite magnetic powder was 0.0961. The Sr / (Ba+Sr) molar ratios are shown in Table 1.
[0041] [Comparative Examples 2 to 6] In Comparative Examples 2 to 6, hexagonal ferrite magnetic powder was manufactured by carrying out processes from the preparation of raw material powder to the finishing process under the same conditions as in Comparative Example 1. That is, Comparative Examples 1 to 6 correspond to each manufacturing batch carried out under the same manufacturing conditions. The Sr / (Ba+Sr) molar ratios obtained for the amorphous bodies and hexagonal ferrite magnetic powders obtained in Comparative Examples 2 to 6 are shown in Table 1. Table 1 also shows the difference MAX-MIN between the maximum and minimum values and the standard deviation σ obtained from the Sr / (Ba+Sr) molar ratios in the amorphous bodies and hexagonal ferrite magnetic powders of Comparative Examples 1 to 6.
[0042] [Table 1]
[0043] As can be seen from Table 1, the difference MAX-MIN between the maximum and minimum values of the Sr / (Ba+Sr) molar ratio measurements and the standard deviation σ in Examples 1 to 6 according to the manufacturing method of the present invention were significantly smaller than those in Comparative Examples 1 to 6 for both the amorphous body and the finally obtained hexagonal ferrite magnetic powder. In other words, by adopting the kneading process, it was possible to significantly reduce the composition variation between manufacturing batches. This is expected to have an effect of improving the variation in the magnetic properties of magnetic recording media.
Claims
1. a kneading step of kneading a raw material powder containing components for forming an amorphous body for synthesizing hexagonal ferrite with water to obtain a kneaded mixture; A granulation step of granulating the kneaded mixture to obtain a granular compact; a heat-melting step of heating the granular compact to obtain a molten compact; a quenching step of quenching the molten body to obtain an amorphous body; A method for producing an amorphous body for synthesizing hexagonal ferrite comprising the steps of:
2. 2. The method for producing an amorphous material for synthesizing hexagonal ferrite according to claim 1, further comprising a drying step of drying the granular compact obtained in the granulation step prior to the heat-melting step.
3. 2. The method for producing an amorphous material for synthesizing hexagonal ferrite according to claim 1, wherein in the kneading step, water is kneaded in a mixing ratio of 20 parts by mass or more and 35 parts by mass or less per 100 parts by mass of the raw material powder.
4. 2. The method for producing an amorphous body for synthesizing hexagonal ferrite according to claim 1, wherein the raw material powder contains Ba and Sr for forming an amorphous body for synthesizing strontium-containing hexagonal barium ferrite.
5. A firing step of synthesizing hexagonal ferrite crystals by heating the amorphous body obtained by the method for producing an amorphous body for synthesizing hexagonal ferrite according to any one of claims 1 to 4 to obtain a hexagonal ferrite-containing powder; a residual component removing step of removing residual components other than hexagonal ferrite from the hexagonal ferrite-containing powder; A method for producing a hexagonal ferrite magnetic powder having the above structure.
6. A preliminary heat treatment step of heating the amorphous material containing Ba and Sr obtained by the method for producing an amorphous material for synthesizing hexagonal ferrite according to claim 4 to a temperature range of 500° C. to 570° C. to obtain an intermediate material; a firing step of synthesizing hexagonal ferrite crystals by heating the intermediate to a temperature range of 600° C. to 670° C. to obtain a hexagonal ferrite-containing powder; a residual component removing step of removing residual components other than hexagonal ferrite from the hexagonal ferrite-containing powder; The method for producing a hexagonal ferrite magnetic powder having the above structure.
7. The method for producing hexagonal ferrite magnetic powder according to claim 6, which obtains strontium-containing hexagonal barium ferrite magnetic powder having a Sr / (Ba+Sr) molar ratio of 0.01 to 0.30.
Citation Information
Patent Citations
Hexagonal ferrite magnetic powder and method of producing molding of raw material for hexagonal ferrite magnetic powder and molding of raw material for hexagonal ferrite magnetic powder
JP2014199870A
Method for producing magnetic raw material for hexagonal ferrite magnetic powder, method for producing compact of magnetic raw material for hexagonal ferrite magnetic powder, and method for producing hexagonal ferrite magnetic powder
JP2015026790A